Development trend of freestyle wrestling: influence of the rule changes on competitive activity - Markovic, M.; Kukic, F.; Zaric, I.; Toskic, L.; Kasum, G.; Dopsaj, M. (International Journal of Wrestling Science, 2020)
This paper deals with wrestling combat performance and how new rule changes have affected competitive activity. Official reports and video material of fights from the European Championships in 2013 (EC2013), before the introduction of the new rules and from the European Championships 2014 (EC2014), First European Olympic Games 2015 (FEOG2015), and European Championships 2020 (EC2020) after the introduction of new rules were analyzed for this study. Fourteen variables were used for evaluation of the competitive activity of wrestlers. Average fight time and points per action increased after EC2013, while a lower number of passivities and total points occurred at EC2013 compared to EC2014, FEOG2015 and EC2020. The number of 1-point actions was significantly higher, while the number of 2-point actions was significantly lower at EC2013 than afterwards. The number of actions worth 3-5 points was lower only when EC2013 was compared to EC2020. The number of actions per match remained unchanged. Average action value was lower at EC2013 than afterwards, intensity of scored points was lower at EC2013 than at the EC2014, while intensity of performed actions was higher at EC2013 than afterwards. A greater sum of points was noticed after EC2013, while the number of actions per match remained the same. The number of actions remaining unchanged despite the duration of matches increasing would indicate that the changes in rules may negatively affect attractiveness.